Ответ: ( 7 ; - 8 ) .
Пошаговое объяснение: { 2x + y = 6 ,
{ 3x +2y =5;
1 - e рівняння домножаємо на ( - 2 ) і додаємо до 2 -го :
{ -4x - 2y = -12 ,
---------------------------
- x = - 7 ; x = 7
Із 1 -го рівняння y = 6 - 2x = 6 -2*7 = 6 - 14 = - 8.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: ( 7 ; - 8 ) .
Пошаговое объяснение: { 2x + y = 6 ,
{ 3x +2y =5;
1 - e рівняння домножаємо на ( - 2 ) і додаємо до 2 -го :
{ -4x - 2y = -12 ,
{ 3x +2y =5;
---------------------------
- x = - 7 ; x = 7
Із 1 -го рівняння y = 6 - 2x = 6 -2*7 = 6 - 14 = - 8.